2017
DOI: 10.1051/epjconf/201716300056
|View full text |Cite
|
Sign up to set email alerts
|

Classical dynamical modelling of near-barrier breakup

Abstract: Abstract. The complete fusion of light, weakly-bound nuclides is known to be significantly suppressed with respect to comparable well-bound projectiles or with respect to single barrier penetration model calculations. Strong α-clustering in these light systems mean that they very easily disintegrate into clusters, either via direct excitation of their intrinsic cluster continuum, or via transfer reactions which connect to unbound states in neighbouring nuclides. This breakup is thought to reduce the probabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The idea that breakup capture should peak backward of no-capture breakup is confirmed by classical dynamical model simulations of breakup [24]. The simulation was constrained to reproduce the individual no-capture breakup total cross sections (σ αα , σ αt , σ αd , σ αp ) as well as the measured relative energy distributions of the breakup fragments [20,21,28].…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…The idea that breakup capture should peak backward of no-capture breakup is confirmed by classical dynamical model simulations of breakup [24]. The simulation was constrained to reproduce the individual no-capture breakup total cross sections (σ αα , σ αt , σ αd , σ αp ) as well as the measured relative energy distributions of the breakup fragments [20,21,28].…”
mentioning
confidence: 91%
“…The amount of breakup capture occurring at abovebarrier energies can then be estimated using classical trajectory models [23,24]. Some works have suggested that breakup capture fully accounts for the suppression of complete fusion [19,25,26].…”
mentioning
confidence: 99%
See 1 more Smart Citation